A semantic approach for automated test oracle generation. (April 2016) - Guo, Hai-Feng
Abstract: This paper presents the design, implementation, and applications of a software testing tool, TAO, which allows users to specify and generate test cases and oracles in a declarative way. Extended from its previous grammar-based test generation tool, TAO provides a declarative notation for defining denotational semantics on each productive grammar rule, such that when a test case is generated, its expected semantics will be evaluated automatically as well, serving as its test oracle. TAO further provides a simple tagging mechanism to embed oracles into test cases for bridging the automation between test case generation and software testing. Two practical case studies are used to illustrate how automated oracle generation can be effectively integrated with grammar-based test generation in different testing scenarios: locating fault-inducing input patterns on Java applications; and Selenium-based automated web testing. Abstract : Highlights: TAO provides a declarative framework for automated test and oracle generation. TAO integrates test and oracle generation as a whole to promote better automated software testing. TAO is the first attempt to apply the methodology of denotational semantics in test and oracle generation.